The Confessional Diversity of 16th-century Polish Religious Lexis: Recapitulation and Research Postulates - Woźniak, Ewa (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2023)
The author summarises the research conducted so far on the confessional differentiation of Polish religious lexis in the 16th century, which was initiated in the 1960s by Konrad Górski, a literary historian. In his publication Zagadnienia słownictwa reformacji polskiej (The Issue of the Polish Reformation Vocabulary), the scholar argued that Protestants used different words than Catholics to designate important religious concepts, and that lexis was an important factor to identify the denomination. This thesis had a significant impact on the assumptions and research objectives formulated by subsequent scholars who addressed the relationship between denomination and vocabulary. In the section of the article containing research postulates, attention is drawn to the necessity of verifying Górski’s position, which was already initiated to a limited extent, mainly in the works by Tomasz Lisowski, who pointed out other than confessional determinants of lexical choices in the 16th-century translations of the Bible. It is considered necessary in the postulated research to broaden the resource base, to take into account the pragmatic diversity of the source texts (sender-receiver relations, intentions), to introduce numerical data objectifying the conclusions, as well as a comparative reference to the status in other languages.